Pembelajaran Matematika dengan Student Team Achievement Division dan Numbered Head Together terhadap Hasil Belajar Ditinjau dari Kemampuan Awal Siswa SMP - Sumardi, S. (Universitas Muhammadiyah Surakarta, 2017)
This research is aimed to examine 1) to analyze and examine the influence of STADand NHT learning strategic toward the learningresult, 2) to analyze and examinethe influence of the beginning ability toward the learning result, 3) to analyzeand examinethe interaction of learning strategic and the beginning ability towardthe mathematic learning result. The research design is Experimental Quasi.Thepopulationof this research was all the seventh year students of SMP N 1 NguterSukoharjo. The removal of the sample is bycluster sampling. The method of the datacollecting is by documentation and test. The population of the research is all studentsof seven grade of SMP N 1 Nguter in 2015/2016 that consist of eigh classes. Theanalysis technic is two ways of different cell Anava, to be continued with Scheffemethod. The result of the research by the significance level 0,05 shows 1) The studentslearning result with STAD strategic isbetter than NHT, 2) The students learning resultof the high beginning ability is better than the students who have medium and lowbeginning ability, the students learning result of the medium beginning ability is betterthan the students who have low beginning ability, 3) STAD strategic is more effectivethan NHT to the students who have medium beginning ability. Concerning with STADstrategic, the learning result of the students who have high beginning ability is assame as the students who have medium beginning ability, and the learning result ofthe students who have high and medium beginning ability is better than the studentswho have low beginning ability. While on the NHT strategic, the learning result ofthe students who have high beginning ability are better than the students who havemedium and low beginning ability. Whereas the students who have medium and lowbeginning ability got the same learning result.